2021
DOI: 10.1021/acsaelm.1c00157
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Ionic Liquid: Key to Efficient Detection and Discrimination in Organic Semiconductor Gas Sensors

Abstract: Π-conjugated polymers (π-CPs) blended with ionic liquids (ILs) have shown great potential for noninvasive diagnostics by transducing dielectric environmental changes induced by volatile organic compound (VOC) biomarkers into distinct electrical signals. However, the role of ILs in VOC sensing remains unclear, limiting further development of organic sensors for real commercialization. Herein, the key VOC detection and discrimination mechanisms in π-CP:IL sensors are identified. Three different ILs forming eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Previous studies with solid‐state ionic liquids confirm that SSIL is an insulator and an SSIL only device measures no current. [ 13 ] The solid‐state nature of the ionic liquid in a solid‐state thin film means there is no ion mobility and electrochemical impedance spectroscopy measurements show there is no ionic contribution to the conductivity increase, Figure S5, Supporting Information. [ 36,37 ] This confirms SSIL as an active component in the current enhancement through reversible interactions with the polymer under an applied bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with solid‐state ionic liquids confirm that SSIL is an insulator and an SSIL only device measures no current. [ 13 ] The solid‐state nature of the ionic liquid in a solid‐state thin film means there is no ion mobility and electrochemical impedance spectroscopy measurements show there is no ionic contribution to the conductivity increase, Figure S5, Supporting Information. [ 36,37 ] This confirms SSIL as an active component in the current enhancement through reversible interactions with the polymer under an applied bias.…”
Section: Resultsmentioning
confidence: 99%
“…The specific properties of the ionic liquid have been explored, revealing the advantage of the solidstate semi crystalline nature of [C 1 C 12 IM + ][PF 6 − ] over amorphous ionic liquids . [13] The polymer properties were investigated in both a high mobility electron donor-electron acceptor (D-A) conjugated copolymer [14] and in the model homopolymer poly(3hexylthiophene-2,5-diyl) (P3HT), with the importance of molecular weight and regioregularity being investigated. [15] Using this conjugated polymer:solid-state ionic liquid blend system, longlived stable polarons in the solid-state are formed via electrochemical doping.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, various strategies for detecting VOCs, such as molecular engineering, 56 surface functionalization (e.g., receptors 57 and porous materials 58 ), morphology control (e.g., porosity 59 and grain boundary 60 ), and heterojunction, 61 have been reported. Among the many known VOCs (e.g., ammonia, 62−66 nitrogen dioxide (NO 2 ), 67−70 hydrogen sulfide (H 2 S), 71,72 toluene, 73 acetone, 74 and formaldehyde 59 ), NO 2 is one of the most intensively targeted gases because it can directly damage human health at ppm levels; moreover, NO 2 is the cause of many environmental problems. To effectively monitor NO 2 gas, Jin et al demonstrated an ionotronic gas-sensing sticker (IGS) that showed particularly high selectivity for NO 2 and can be used as a wearable gas-sensing platform.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…Among the many known VOCs (e.g., ammonia, nitrogen dioxide (NO 2 ), hydrogen sulfide (H 2 S), , toluene, acetone, and formaldehyde), NO 2 is one of the most intensively targeted gases because it can directly damage human health at ppm levels; moreover, NO 2 is the cause of many environmental problems. To effectively monitor NO 2 gas, Jin et al demonstrated an ionotronic gas-sensing sticker (IGS) that showed particularly high selectivity for NO 2 and can be used as a wearable gas-sensing platform .…”
Section: Chemical Sensorsmentioning
confidence: 99%